Organoid drug screening report for a non-small cell lung cancer patient with EGFR gene mutation negativity: A case report and review of the literature - Pan, Yuetian; Cui, Hongshang; Song, Yongbin (Frontiers in Oncology, 2023)
Patients with non-small cell lung cancer (NSCLC) who carry epidermal growth factor receptor (EGFR) mutations can benefit significantly from EGFR tyrosine kinase inhibitors (EGFR TKIs). However, it is unclear whether patients without EGFR mutations can not benefit from these drugs. Patient-derived tumor organoids (PDOs) are reliable in vitro tumor models that can be used in drug screening. In this paper, we report an Asian female NSCLC patient without EGFR mutation. Her tumor biopsy specimen was used to establish PDOs. The treatment effect was significantly improved by anti-tumour therapy guided by organoid drug screening.